The Principle of Equality in Labour Law - Jovanović, Predrag (Zbornik radova Pravnog fakulteta u Novom Sadu, 2018)
The principle of equality in labour law, i.e, in the field of employment and work, means the equality of chances in achieving socio-economic rights in that field and equal opportunities in title and protection of such rights. This principle has three aspects (elements): firstly, the equality of chances in achieving socio-economic rights and equalities when getting title and protecting those rights, as the main and affirmative substratum of this principle; secondly, the prohibition on discrimination when achieving and protecting socio-economic rights, as the protective element of equality and equal opportunities; thirdly, positive discrimination when getting title to and protecting socio-economic rights, as a legitimate addition to the prohibition on discrimination. The principle of equality can be purposeful only by parallelly exposing all of the named aspects. In other words, the equality aspect of chances and equal opportunities when getting title to certain rights is provided by prohibiting discrimination, and the prohibition on discrimination is provided and accompanied by positive discrimination. Due to its significance, the priniciple of equality is encompassed in many legal documents (international, European and domestic), and in the light of which this principle is shown in the three named aspects (elements).